Addressing the Social Determinants of Health: A Call to Action for School Nurses. (June 2018) - Schroeder, Krista; Malone, Susan Kohl; McCabe, Ellen; Lipman, Terri
Social determinants of health (SDOH), the conditions in which children are born, grow, live, work or attend school, and age, impact child health and contribute to health disparities. School nurses must consider these factors as part of their clinical practice because they significantly and directly influence child well-being. We provide clinical guidance for addressing the SDOH when caring for children with three common health problems (obesity, insufficient sleep, and asthma). Given their unique role as school-based clinical experts, care coordinators, and student advocates, school nurses are well suited to serve as leaders in addressing SDOH.